RAINFALL MONITORING IN URBAN AREAS IN THE AMAZON USING WEATHER RADAR ON THE SIPAMHIDRO PLATFORM - Carvalho Barreto, Cairo Eduardo; Altieri dos Santos, Flávio Augusto; Lopes Monteiro, Raquel Macêdo; Souza dos Reis, Jean; Paulino da Rocha, Edson José (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
Meteorological radar allows the monitoring and prediction in short and very short-term time intervals of storm movement. The objective of this research is to evaluate the weather radar effectiveness for extreme precipitation events forecasting using the SipamHidro rainfall in urban area application. This assessment was carried out considering the storm that occurred in Manaus on March 25, 2023. Observations from pluviometers installed in the urban area of Manaus by CEMADEN and estimated precipitation determined using the TITAN software were used. The evaluation was based on Pearson correlation coefficient, cartographic representations and comparison between observed and predicted. The results show that: a) The event generated more than 135 occurrences of disasters due to extreme rain in the city of Manaus; b) forecasts obtained by radar tend to underestimate observed precipitation by between 31% and 72%, but their spatial distribution is similar; c) the correlations between precipitation obtained by radar and observed precipitation in neighborhoods with rain gauges were from r= 0.59 a r= 0.95, except at the nearby area of the radar; d) the analysis between the predicted and observed times indicates a tendency to adequately anticipate the start of the storm. There were significant correlations between radar data and rain gauges, except in the vicinity of the radar. Despite the lack of precision in extreme rainfall measurements, radar has shown potential as an early forecasting tool, highlighting the importance of its continued development to improve the response to extreme events in urban areas.